PERAN DAN TUGAS KEPALA SEKOLAH DALAM MANAJEMEN KURIKULUM DI TK IT MADANI RUPAT UTARA - Hikmatul Hidayah (Universitas Islam Negeri (UIN) Sumatera Utara, 2022)
This study aims to describe the role of the principal in curriculum management in TK IT Madani Rupat Utara. In line with the research objectives, this research uses descriptive qualitative research methods. To obtain the data needed, the author uses 3 (three) data collection techniques, namely: 1. Interview, 2. Observation, 3. Documentation. The results of the research on the role and duties of the principal towards his school are very important and greatly affect the existence of the IT Madani Kindergarten in the future. The principal is not just how to improve the school internally but also externally, for example by building relationships with other parties. So that the principal is called an educator because he must be able to educate and follow up every student and student. Principals are also referred to as managers and leaders in their schools because the principal's main authority is to make decisions. So that in this curriculum management the principal is the principal. The role of the principal as a school leader has the responsibility to mobilize all existing resources in the existing school so as to give birth to a work ethic and high productivity in teaching and learning activities